Optimal UX/UX Design Through Lean UX Methodology: MTI Pay Case Study - Putra, Handie Pramana; Salim, Agus (Universitas Pendidikan Indonesia, 2024)
This research explores the transformative journey of MTI Pay in response to the challenges posed by technology and globalization in the competitive banking industry. The study delves into the impacts of these global shifts, emphasizing the emergence of numerous startup companies and the imperative for businesses to innovate within limited resources. In addressing this, MTI Pay introduces a super bank, leveraging advanced technology to create a personalized and easily accessible banking experience. The design process of MTI Pay employs the Lean UX method, a contemporary approach to user experience development rooted in Agile principles. This method, focusing on user-centric design, iterative development, and efficiency, aligns with the need for adaptability in a rapidly changing technological landscape. The study concludes with optimism about the positive impact of implementing Lean UX, anticipating improved user experiences and overall system enhancement.In essence, MTI Pay strategically positions itself to thrive in the evolving banking industry, with a commitment to innovation, adaptability, and user satisfaction. The research underscores the significance of such strategic approaches in navigating the complexities of modern banking within a globalized and technologically advanced era.